HUBUNGAN KELENTUKAN PINGGANG TERHADAP KEMAMPUAN PUKULAN ROUND THE HEAD CLEAR PEMAIN BULU TANGKIS PB STARKA KECAMATAN KAYU ARO - Luky Afriandika; Jonika Trishandra; Yonsisno (EDU RESEARCH, 2023)
Based on the author's observations so far, it appears that the ability of athletes at PB. STARKA Kayu Aro District in hitting round the head clear is said to be moderate. There are those who have good waist flexibility but when hitting round the head clear shots are not also good. This can be seen from the frequent retrieval of Shuttlecock from this round the head clear shot, the shuttle falls in the middle of the opponent's field or responsibility, the shuttle is mostly out (out) instead of this round the head clear shot the shuttle falls at the back of the opponent's field. Based on the description above, on this occasion the author tries to look further at the relationship of waist flexibility, to the ability to hit round the head clear badminton club PB players. STARKA Kayu Aro District. This study aims to determine the relationship between waist flexibility and the ability to hit round the head clear players Club PB. STARKA Kayu Aro Subdistrict. The research method used in this research is correlation. Correlation is to determine the relationship or interdependence between two or more variables. Population is the whole object of research. The population in this case is PB athletes. Starka Kayu Aro District which totalled 16 people. Furthermore, the researchers took a sample in this study of 10 PB players. Starka Kayu Aro District. Sampling in this study was carried out by measuring waist flexibility against the ability to hit Round The Head Clear. To obtain data in this study, tests were conducted on PB club players. Starka Aro wood sub-district. The form of the test carried out in this study is a test of the ability to hit round the head clear. Where when the taster hits round the head clear then counts how many values are obtained. The instrument used to measure waist flexibility is the sit and reach test, the way of assessment is to record the ability to reach from athletes. The hypothesis test used in this study is the product moment correlation test but previously the normality test and variance homogeneity test were carried out. Based on the results of the research that has been described, it can be stated that the results of data processing obtained sig. (2-tailed) = 0.002 < ∝ = 0.05 means that H0 is rejected and H1 is accepted so that it can be concluded that there is a significant relationship between waist flexibility and the ability to hit Round The Head Clear Badminton Club PB players. Starka Kayu Aro District.